Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/ijms232012522
|View full text |Cite
|
Sign up to set email alerts
|

Reactive Centre Loop Mutagenesis of SerpinB3 to Target TMPRSS2 and Furin: Inhibition of SARS-CoV-2 Cell Entry and Replication

Abstract: The SARS-CoV-2 virus can utilize host cell proteases to facilitate cell entry, whereby the Spike (S) protein is cleaved at two specific sites to enable membrane fusion. Furin, transmembrane protease serine 2 (TMPRSS2), and cathepsin L (CatL) are the major proteases implicated, and are thus targets for anti-viral therapy. The human serpin (serine protease inhibitor) alpha-1 antitrypsin (A1AT) shows inhibitory activity for TMPRSS2, and has previously been found to suppress cell infection with SARS-CoV-2. Here, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Indeed, α1AT is the most abundant inhibitor of NSPs in plasma and α1AT deficiency (AATD) is the most important genetic predisposition to emphysema and chronic obstructive pulmonary disease, where proteases drive the pathology. Moreover, α1AT binds to TMPRSS2 at high concentrations, impairing S processing by TMPRSS2 and preventing SARS-CoV-2 entry to some extent (48)(49)(50)(51). Our results, however, challenge the notion that reduction of JCI Insight 2024;9(7):e174133 https://doi.org/10.1172/jci.insight.174133 NSP activity is a critical target in severe COVID-19 patients and our data are supported by recent epidemiological and clinical trial results.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, α1AT is the most abundant inhibitor of NSPs in plasma and α1AT deficiency (AATD) is the most important genetic predisposition to emphysema and chronic obstructive pulmonary disease, where proteases drive the pathology. Moreover, α1AT binds to TMPRSS2 at high concentrations, impairing S processing by TMPRSS2 and preventing SARS-CoV-2 entry to some extent (48)(49)(50)(51). Our results, however, challenge the notion that reduction of JCI Insight 2024;9(7):e174133 https://doi.org/10.1172/jci.insight.174133 NSP activity is a critical target in severe COVID-19 patients and our data are supported by recent epidemiological and clinical trial results.…”
Section: Discussionmentioning
confidence: 99%
“…Given the exceptional proteomic diversity present within the pan-species protease/ antiprotease spectrum, the best actionable evidence might emerge from a confluence of corroborating evidence, such as exacerbatory or inhibitory roles of bacterial species that also encode proteases or antiproteases similar to COVID-19-related host proteins. As evidence of this, it should be noted that experimental mutagenetic manipulation of human SERPINb3 transformed an antiprotease with minimal capacity for TMPRSS2 inhibition into a TMPRSS2 blocker more potent than SERPINa3 [179]. Since evolutionary pressures can foster rapid bacterial mutations, it is possible that some forms of bacteria may have adapted their proteolytic capacity for the purpose of modifying human TMPRSS2 activity, as suggested in studies relating to the synergistic interplay among TMPRSS2, androgen control, and microbiome composition [180][181][182][183].…”
Section: Microbiotic Mimicry and Amplification Of Protease/antiprotea...mentioning
confidence: 99%
“…A three-dimensional lung cell model using primary cells from multiple donors found that more resistant donors to an in vitro SARS-CoV-2 infection expressed higher transcript levels of SERPINA1 (AAT gene), SERPINE1, and SERPINE2 in the airway cells [70]. Variants of SerpinB3-through mutagenesis of its RCL-have been generated and found to be more potent in inhibiting TMPRSS2 than AAT [71]. We found that the AAT inhibition of TMPRSS2 activity in primary hAEcs was augmented significantly by enoxaparin [18].…”
Section: Furin Tmprss2 and Their Inhibition By Aat In The Context Of ...mentioning
confidence: 99%